VARIABILITY OF CARAPACE WIDTH SIZE AND ABUNDANCE OF BLUE SWIMMING CRABS (Portunus pelagicus Linnaeus) IN PATI WATERS (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Fishing effort enhancement would put pressure on blue swimming crab resources and its ecosystem. The objective of this study was to determine the spatial distribution based on the size of the carapace width (CW), abundance, temperature, salinity, depth, and fishing intensity in Pati waters which was divided into two zones (zones 1=nearshore, zone 2=offshore). The result showed that the average of carapace width in zone 1 to zone 2 was significantly different (p